Analisis Bentuk Dan Makna Reduplikasi Koran Karawang Bekasi Ekspres Edisi Mei 2023 - Devi, Tri; Sutri, Sutri; Muhtarom, Imam (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research is motivated by a lack of understanding about reduplication which can be used as an activity in language. The purposes of this study are 1. To describe the form and meaning of reduplication in the May 2023 edition of the Karawang Bekasi Ekspres newspaper, the Education & Sports column. The method used in this research is descriptive qualitative. The subjects in this study were the May 2023 Edition of the Karawang Bekasi Ekspres newspaper. Data collection techniques in this study were observation, literature study, listening, reading and taking notes, and documentation. Researchers conducted an analysis of form and meaning reduplication in the May 2023 Edition of the Karawang Bekasi Ekspres newspaper. The tools used to collect data were laptops, mobile phones, theory books, notebooks and writing instruments. The results of the study found 22 repeated words in the May 2023 Edition of the Karawang Bekasi Express newspaper which were analyzed in full.